2018
DOI: 10.14302/issn.2641-4538.jphi-18-2470
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diarrhea and Associated Factors among Under Five Years Children in Harena Buluk Woreda Oromia Region, South East Ethiopia, 2018

Abstract: Background: Acute diarrheal diseases are the leading cause of preventable childhood death, especially in developing countries. It is the second leading cause of death in under-five year children nest to pneumonia. Objectives: The aim of this study was to determine the magnitude and associated factors of diarrhea in under-five in Harena Buluk district. Methods: A community based Cross sectional study was conducted in February, 2018. A two stage stratified sampling method was done to select the eligible househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
12
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
8
12
2
1
Order By: Relevance
“…The finding of this study indicated that children from parents/legal guardians who did not practice hand washing during the critical time were affected with diarrheal disease 10.6 times more likely compared to those children whose parents/legal guardians have practiced hand washing during a critical time. This finding was in line with the studies conducted in Adama Rural and Harena Buluk woreda in Ethiopia (28,29) and in Zambia (30). This might be indicated that since the parents/legal guardians were the main caregivers for their children they should wash their hands at a critical time to prevent diarrheal diseases.…”
Section: Socio-demographic Characteristics Of Study Participantssupporting
confidence: 87%
“…The finding of this study indicated that children from parents/legal guardians who did not practice hand washing during the critical time were affected with diarrheal disease 10.6 times more likely compared to those children whose parents/legal guardians have practiced hand washing during a critical time. This finding was in line with the studies conducted in Adama Rural and Harena Buluk woreda in Ethiopia (28,29) and in Zambia (30). This might be indicated that since the parents/legal guardians were the main caregivers for their children they should wash their hands at a critical time to prevent diarrheal diseases.…”
Section: Socio-demographic Characteristics Of Study Participantssupporting
confidence: 87%
“…Furthermore, this study shows that unemployment [ 48 ], low economic status, and lack of access to media gadget such as television and radio among mothers are associated with the risk of their children developing diarrhoea [ 49 ]. As affirmed by other studies, an average weighted child at birth [ 41 ] firstborns [ 46 ] and children born to parents with low access to infrastructural facilities such as improved toilet [ 50 ] and improved housing materials have a higher risk of diarrhoea occurrence. Access to improved toilet facilities allows for safer disposal of faeces and limit the risk of contact between diarrhoea causative organism and human host [ 2 ].…”
Section: Discussionmentioning
confidence: 87%
“…This finding was congruent with the study done in Dale District, Sidama zone, Southern Ethiopia, 13.9% [11], Yaya Gulele district, Ethiopia 13.5% [15], Serbo town, Southwest, Ethiopia, 14.9% [16], Bahr Dar city, 14.5% [17], and Farta Wereda, Northwest Ethiopia, 16.7% [7]. However, result of this study was lower than the study conducted in Sena'a, Yemen, 29.07% [18], Senegal, 26% [19], Cameroon, 26.1% [20], Sheka zone, southwest Ethiopia, 21.8% [12], Jig-Jiga city, Eastern Ethiopia, 27.3% [21], Bahir Dar Zuria district, Northwest Ethiopia, 20% [22], North Gondar zone, 21.1% [10] and Harena Buluk district, Southeast Ethiopia, 28.4% [23]. In contrast, it was higher than the study conducted in Wolayta Sodo town, Southern Ethiopia, 11.0% [24].…”
Section: Discussionmentioning
confidence: 99%